Efek Hook pada Prolaktinoma: Tantangan Diagnosis pada Remaja dengan Galaktorea dan Amenore - Fara Julyta Aliyah; Rijal Bulqini (Pusat riset dan Inovasi Nasional, 2026)
Prolactinoma is the most common functional pituitary adenoma, particularly in adolescent females, and is typically characterized by amenorrhea and galactorrhea resulting from hyperprolactinemia. However, in certain cases, serum prolactin levels may appear normal due to the hook effect, an immunoassay measurement error caused by extremely high prolactin concentrations that interfere with antigen–antibody complex formation. We report the case of a 17-year-old female presenting with a five-month history of galactorrhea, accompanied by breast pain, headache, and primary amenorrhea. Brain MRI revealed a pituitary mass measuring 1.4 × 0.8 × 0.5 cm, suspicious for prolactinoma, while serum prolactin was within the normal range (17.33 ng/mL). The discrepancy between clinical manifestations, lesion size, and laboratory findings raised suspicion of the hook effect. The patient was treated with dopamine agonists, bromocriptine and cabergoline, and referred for multidisciplinary management involving endocrinology, neurosurgery, and obstetrics–gynecology. Despite the absence of prolactin dilution testing, MRI findings supported the diagnosis of prolactinoma, and the patient demonstrated a favorable clinical response to therapy. This case highlights the importance of recognizing laboratory variability, performing comprehensive hormonal evaluation, and considering prolactin dilution assays when clinical and laboratory findings are discordant, particularly in adolescent patients with suggestive symptoms.